Comparative study of multiferroic properties of PbTi0.5Fe0.5O3 thin films grown on various substrates. Issue 17 (1st December 2017) - Nawaz, S.; Tulapurkar, A.A.; Palkar, V.R.
Abstract: Multiferroic PbTi0.5 Fe0.5 O3 films are grown by using pulsed laser deposition technique on Si, Pt/Ti/SiO2 /Si and SrRuO3 /Si substrates. It is found that the PbTi0.5 Fe0.5 O3 films get modified from tetragonal to orthorhombic while deposited on Si substrate unlike the other two substrates. For Pt/Ti/SiO2 /Si and SrRuO3 /Si substrates the crystal structure remains tetragonal. More importantly, the magnitude of ferroelectric, magnetic polarization and magneto-electric coupling observed in both tetragonal and orthorhombic phases are good enough for a variety of device applications. It gives flexibility for selecting substrate while fabricating PbTi0.5 Fe0.5 O3 based multifunctional devices.